MicroRNAs: Emerging players in the pathogenesis of vitiligo - Yu, Xin; Cui, Yuli; Zhu, Xueqing; Xu, Hongjun; Li, Linfeng; Gao, Guangcheng (Frontiers in Cell and Developmental Biology, 2022)
Vitiligo is an autoimmune skin disease characterized by presence of pale patchy areas of depigmentation. MicroRNAs (miRNAs) are important regulators of gene expression and play significant roles in diverse biological and pathological processes. Accumulating evidence has shown that miRNAs were differentially expressed in skin lesions and peripheral blood mononuclear cells of patients with vitiligo. In particular, miRNAs are significantly correlated with the development and progression of vitiligo. The abundance of some miRNAs in serum was also correlated with the vitiligo lesion severity, indicating that miRNAs might serve as prognostic biomarkers. Importantly, the direct involvement of miRNAs in the pathogenesis of vitiligo has been demonstrated. For example, increased expression of miR-25 contributes to vitiligo through promoting the dysfunction and oxidative stress-induced destruction of melanocytes. However, there are limited studies on the function and mechanism of deregulated miRNAs in vitiligo. Further studies are required to establish clinical applications of miRNAs for vitiligo. More in-depth investigations of miRNAs are needed for the understanding of the pathogenesis of vitiligo and the development of novel therapeutic targets. This present review summarizes the current literature on the deregulation and pathogenic roles of miRNAs in vitiligo. We also highlight the potential clinical applications of miRNAs in patients with vitiligo.